Views of Hobbes, Locke, and Rousseau in the Origin of the State: A Comparative Analysis - Magar, Rudra Bahadur Pulami (Khwopa Journal, 2025)
From the question of the origin of the state to the broader history of human civilizations, there have been extensive debates about the organization of social life, the interpretation of rights and powers, the legitimacy of morality, and the relationship between citizens and government. This research has attempted to clarify the philosophy of the origin of the state, especially through a comparative study of the social contract theory of three prominent Western philosophers. Hobbes emphasized the need to cede all authority to the sovereign to avoid an anarchic state of nature, in which one sacrifices one’s freedom for security. Locke put forward the concept of a limited state or government that preserves natural right, whereas Rousseau emphasized a state of free and equal citizens founded on the will of the people, thereby transforming the social contract into a moral principle. This research seeks to provide a current interpretation of legitimacy, state, the power structure, and civil rights by deeply philosophically analyzing these principles. This research is based on a historical-philosophical method, which uses textbooks, original articles, and critical perspectives to present a critical review. In addition, it is analyzed to what extent these ideas. It is hoped that the comparative study presented in this way will contribute to contemporary political discourse.